Development of Clean Water Network in Ngasinan Village Bojonegoro Regency - Rozi, Maksum; Sugiarto Waluyo, Budi; Rizal Sutikno, Fauzul (Fakultas Teknik, Universitas Brawijaya, 2024)
Ngasinan Village is one of the areas where clean water distribution is managed by Ngasinan Village Regional Drinking Water Company (PAMDes). There are still several problems, especially regarding the provision of clean water. Currently, the managed clean water network has not reached the entire Ngasinan Village area, with 30.18% still using wells and rain-fed wells. This has an impact when the dry season occurs, which decreases water discharge and causes water scarcity. Therefore, to improve the provision of clean water, Ngasinan village needs to build a comprehensive clean water network for the community. The method was used quantitatively with water demand forecasting analysis techniques and in planning a water network with Epanet 2.0. Based on the forecasting results for 2033, the need for water is 1.92 liters/second, with a standard water requirement of 60 l/day/capita. The average water requirement in 2033 is 2.77 liters/second, including domestic and non-domestic needs. The development plan of Ngasinan Village is to add one water source, namely the Temulus source, with an installed capacity of 7 l/s, which will serve 112 customers. The planned length of the water distribution pipe is 3123.60 meters with a 2-3 inch PVC pipe type, pipe speed in the range of 0.26-0.88 m/s, and pressure in the range of 51.13 - 58.92 m. This study contributes to the clean fulfillment efforts, especially in supporting the 100-0-100 program. Recommendations are given to village policymakers to optimize the existing clean water potential for better clean water services.